Rissepareringens effekter på viltets nyttjandegrad av GROT - Rehmberg, David (2014)
Successful forest regeneration is a prerequisite for sustainable forest management. Therefore, it is important to prevent browsing damage on the commercially important tree species Scots pine. In this study I have tested a new alternative way to increase the available amount of forage and increase the use of these resources by especially moose. The method is based on a slash treatment at harvest, where the accessibility of slash as forage is increased during final felling or commercial thinning by gathering the slash and putting the Scots pine slash on top of the slash piles. This study has compared the availability of forage, the amount of browsed biomass and the number of fecal pellet groups between conventional and slash treated stands after final felling and commercial thinning in southern Sweden. My study could not show any positive effects of the slash treatment on the browsed biomass or pellet group numbers. However, the browsed biomass and number of pellet groups counted in the commercial thinning stands were significantly higher than in the final felling stands. Possible explanations for the results are that the total available forage biomass was not different between the treatments, which would be an indication of that the treatment was not performed well enough. Even though the slash treatment did not change the habitat choice of the moose in this study, it could be that improvements in the slash treatment and choice of objects could actually influence moose forage behavior.